The Influence of Organizational Culture, Participatory Leadership And Intrinsic Motivation On The Affective Commitment of State Junior High School Teachers In Tarutung Sub-District, North Tapanuli District - Lumbantobing, Roida; Panjaitan, Binur; Pakpahan, Betty A. S.; Manurung, John Sihar (the International Journal of Education, Theology, and Humanities, 2025)
This study aims to determine: (1) the positive influence of organizational culture on affective commitment, (2) the positive influence of participative leadership on affective commitment, (3) the positive influence of intrinsic motivation on affective commitment and (4) the simultaneous positive influence of organizational culture, participative leadership on affective commitment of junior high school teachers in Tarutung sub-district, North Tapanuli district. The research population was all junior high school teachers in Tarutung sub-district, totaling 165 people. To determine the sample, a random sampling technique was used. The sample size was determined at 35%, obtained 58 people. The research data were obtained through a questionnaire with a Likert scale weight. The questionnaire was first tested on 30 teachers at Junior High School 1, Siatas Barita Sub-district, North Tapanuli  district,  to determine the validity and reliability of the research instrument. The analysis requirement test includes (1) normality test, using non-parametric statistical test, the data is normally distributed (2) linearity test, the value is more =0.335, =0.581, =0.790 >0.05 (3) multicollinearity test, the standard error value is low and multicollinearity is not detected, (4) relationship test (correlation) is obtained that each variable is related to variable Y. Where  is greater than . The results of the study concluded that (1) organizational culture has a positive effect on affective commitment with an  value of 0.437, meaning that organizational culture has a positive effect on teacher affective commitment of 43.7%, (2) participative leadership on affective commitment, the  value is 0.264, meaning that leadership has a positive effect on teacher affective commitment of 26.4%. (3) intrinsic motivation on affective commitment, the  value is 0.429, meaning that intrinsic motivation has a positive effect on teacher affective commitment of 42.9%, (4) From the results of the F test, it can be concluded that organizational culture, participative leadership and intrinsic motivation simultaneously positive influence affective commitment. The contribution of the three X variables is 25.30%. Thus, it is concluded that organizational culture, participative leadership, and intrinsic motivation simultaneously have a positive effect on the affective commitment of teachers at State Middle Schools in Tarutung Sub-District, North Tapanuli District.